2023
DOI: 10.2147/ijgm.s397550
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Expression of IDH1, ATRX, Ki67, GFAP, and Prognosis in Indonesian Glioma Patients

Abstract: Background The current World Health Organization (WHO) 2021 classification of human glioma is based on key molecular biomarkers to define neoplastic entities. This review further delineates mutant IDH (isocitrate dehydrogenase) from wild-type IDH disease, a necessity given the large survival gap between mutant IDH and wild-type IDH tumors. In Indonesia, there are currently few reports on the distribution and significance of these mutations. Therefore, this research aims to determine the relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
2
1
0
Order By: Relevance
“…Individuals with IDH1 mutations had better outcomes than those without. 44 Consistent with this, we observed that the FS1 patients, who experienced the worst prognosis, did not exhibit any IDH1 mutations. Next, the assessment of the relationship between F-subtypes and TIME was performed.…”
Section: Dovepresssupporting
confidence: 87%
“…Individuals with IDH1 mutations had better outcomes than those without. 44 Consistent with this, we observed that the FS1 patients, who experienced the worst prognosis, did not exhibit any IDH1 mutations. Next, the assessment of the relationship between F-subtypes and TIME was performed.…”
Section: Dovepresssupporting
confidence: 87%
“…Regarding gender distribution, Jakovlevs A observed a slight predominance of females (51.4%), which is in contrast to our study, where the males were more frequently affected by these malignant lesions [23]. Similar to our study, Priambada et [25,26,28,29]. In the study by Alimohammadi E et al, in over 60% of the analysed group, glioblastomas predominantly affected the male sex, and almost 10% of them were IDH-1 mutant glioblastomas [32].…”
Section: Discussionsupporting
confidence: 73%
“…The ATRX mutations occurs at high frequencies in both low-grade gliomas (71%) and secondary GBM (57%) [ 14 ]. Isocitrate dehydrogenase (IDH) mutant GBM with ATRX loss exhibits a higher survival rate than the IDH mutant with the wild-type ATRX gene [ 15 ]. ATRX is a chromatin remodeling protein that plays an important role in the deposition of the histone variant H3.3 [ 16 ].…”
Section: Introductionmentioning
confidence: 99%